Senior w świecie mediów - TRZCIŃSKA-KRÓL, MARIA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Maria Trzcińska-Król, Senior w świecie mediów [Seniors in the media world]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 22, Poznań 2018. Pp. 51-71. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.04 Nowadays, the media education process begins at a very early stage of life and lasts throughout life. Older people are still in a worse position in this respect. In order to find a place in the information society, they have to master the IT and media skills and competences that allow not only to use new forms of education (e.g. e-learning, distance learning, blended learning), but also to an ever greater extent to handle everyday affairs. (e.g. making a payment, booking a ticket, settling a case at the office). The key role is played by education, computer and internet training and non-institutional support. Among the most frequently cited reasons for not using technology, researchers mention the lack of: motivation; access to media, the Internet; competence; awareness of how, for what use ICT can be used. The main obstacles in the dissemination of new technologies to the public are not hard barriers, like lack of infrastructure or financial constraints, but soft, related to the lack of: knowledge, conscious needs or skills.